Institutional Leadership Pattern Islamic Boarding School - Abdul Rahman Munir Aritonang (-, 2022)
Islamic boarding schools have a big role in the education system in Indonesia. In addition, it is also influential in shaping and maintaining social, cultural, political, and religious life. The purpose of writing this article is to find out the pattern of institutional leadership of Islamic Boarding Schools in Indonesia. This study uses a qualitative method with a descriptive approach. Data collection using library research method. The data analysis technique used a descriptive approach. The discussion in this article includes: the concept of leadership, leadership functions, types of leaders and leadership profiles of kiyai, dynamics of kiyai leadership in Islamic boarding schools, and decision-making techniques.